Pension Funds: Issues and Alternatives: Discussion - Attwood, James A. (Journal of Finance, 1968)
James A. Attwood, Pension Funds: Issues and Alternatives: Discussion, The Journal of Finance, Vol. 23, No. 2, Papers and Proceedings of the Twenty-Sixth Annual Meeting of the American Finance Association Washington, D.C. December 28-30, 1967 (May, 1968), pp. 344-347